PERSON DEIXIS AND ITS CULTURAL IMPLICATIONS IN ENGLISH AND UZBEK TEXTS - Boltaqulova Gulnoza Farruxovna,; Rabbimova Sitora Ravshan qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
ANNOTATION:  This  article  examines  person  deixis  in  English  and  Uzbek writings through a cultural and pragmatic lens. Person deixis, encompassing pronouns and  other  references  to  individuals  in  conversation,  significantly  influences interpersonal relationships and conveys social hierarchy. The research analyzes the utilization of  first, second,  and third person  deixis by  English  and  Uzbek  speakers across different textual settings, such as conversations, brief texts, and social media updates. Particular emphasis is placed on the cultural effects of person deixis, including strategies  for  politeness,  levels  of  formality,  and  social  distance.  Comparative examination  shows  both  resemblances  and  distinctions  in  how  the  two  languages convey social relationships and cultural standards through person deixis. The results enhance  comprehension  of  cross-cultural  communication  and  pragmatic  skills  in multilingual settings